Viewpoints on recognition and education - Tom Ritchie (Revista Complutense de Educación, 2007)
This article focuses on the role of Recognition in educational contexts and attempt the legitimation of its significance so that in every teaching situation the affective and sensitive education. A commitment for the cognitive development and for the own selves of the students is recommended. This implies to look at several elements sometimes neglected –as the emotions or the spirituality–, that however encourages already in pre-school institutions in order to improve the identity of young people as a whole person. To pay attention to the relationships with others and to create a supportive environment in the classroom is a way to improve the academic performance and the child’s learning, that becomes more holistic and independent of the adult’s perspective